2012
DOI: 10.1074/jbc.m111.271528
|View full text |Cite
|
Sign up to set email alerts
|

Large Putative PEST-like Sequence Motif at the Carboxyl Tail of Human Calcium Receptor Directs Lysosomal Degradation and Regulates Cell Surface Receptor Level

Abstract: Background: Regulation of cell surface expression and signaling activity of the calcium-sensing receptor plays an important role in human diseases. Results: A PEST-like degradation motif participates in routing of the receptor to the lysosomal pathway. Conclusion: This degradation motif regulates cell surface receptor abundance. Significance: This might be a novel mechanism that connects lysosomal degradation and regulation of cell surface receptor expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…CaSR is the closest related mammalian receptor of GPRC6A and has proven highly resistant to desensitization, which most likely reflects a persistent exposure to the endogenous agonist Ca 2ϩ (50,51). Constitutive internalization of CaSR has been observed in some studies (52,53), and moreover, a distinct regulatory mechanism for CaSR has been reported in which agonist stimulation triggers further insertion of receptors in the cell membrane from intracellular stores, thereby increasing the amount of receptors available for activation. This mechanism has been named agonist-driven insertional signaling (54).…”
Section: Discussionmentioning
confidence: 99%
“…CaSR is the closest related mammalian receptor of GPRC6A and has proven highly resistant to desensitization, which most likely reflects a persistent exposure to the endogenous agonist Ca 2ϩ (50,51). Constitutive internalization of CaSR has been observed in some studies (52,53), and moreover, a distinct regulatory mechanism for CaSR has been reported in which agonist stimulation triggers further insertion of receptors in the cell membrane from intracellular stores, thereby increasing the amount of receptors available for activation. This mechanism has been named agonist-driven insertional signaling (54).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports suggest that CaSR endocytosis is rapid, constitutive, and facilitated by Rab7 and Rab11a. 68,84 Recycling of the CaSR has been noted in some studies 68,84 but not in others, 63 suggesting that the constitutive receptor internalization may require a different endocytic machinery. The CaSR endocytosis is essential for the transactivation of epidermal growth factor receptor that leads to the MAP kinase signaling cascade and links receptor signaling to PTH-related peptide secretion via a Rab11a-dependent and associated molecule with the SH3 domain of STAM (AMSH)-sensitive mechanism.…”
Section: Endocytosis and Recycling Of Casrmentioning
confidence: 94%
“…A long PEST-like sequence motif (rich in proline, glutamine, serine and threonine) within amino acids 920-970 of the C-tail directs lysosomal degradation and regulates cell surface receptor level (30) with the latter property also influenced by an arginine-rich motif, R890-R898 (31). A leucine 1013, leucine 1014 motif in the CASR ICD interacts with the multi-subunit adaptor protein 2 (AP-2) that mediates endocytosis of the CASR.…”
Section: Discussionmentioning
confidence: 99%